The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.3389/fmicb.2018.00901
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Loss of ABC Transporter Genes From Clostridioides difficile Genomes Is Associated With Impaired Tyrosine Uptake and p-Cresol Production

Abstract: We report the frequent, convergent loss of two genes encoding the substrate-binding protein and the ATP-binding protein of an ATP-binding cassette (ABC) transporter from the genomes of unrelated Clostridioides difficile strains. This specific genomic deletion was strongly associated with the reduced uptake of tyrosine and phenylalanine and production of derived Stickland fermentation products, including p-cresol, suggesting that the affected ABC transporter had been responsible for the import of aromatic amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 52 publications
(81 reference statements)
0
27
0
Order By: Relevance
“…For Illumina sequencing, genomic DNA was extracted from bacterial isolates by using the DNeasy Blood and Tissue kit (Qiagen), and libraries were prepared as described previously [46] and sequenced on an Illumina NextSeq 500 machine using a Mid-Output kit (Illumina) with 300 cycles. For generating complete genome sequences, we applied SMRT long-read sequencing on an RSII instrument (Pacific Biosciences) in combination with Illumina sequencing as reported previously [46]. All genome sequencing data were submitted to the European Nucleotide Archive (www.ebi.ac.uk/ena) under study numbers PRJEB33768, PRJEB33779 and PRJEB33780.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For Illumina sequencing, genomic DNA was extracted from bacterial isolates by using the DNeasy Blood and Tissue kit (Qiagen), and libraries were prepared as described previously [46] and sequenced on an Illumina NextSeq 500 machine using a Mid-Output kit (Illumina) with 300 cycles. For generating complete genome sequences, we applied SMRT long-read sequencing on an RSII instrument (Pacific Biosciences) in combination with Illumina sequencing as reported previously [46]. All genome sequencing data were submitted to the European Nucleotide Archive (www.ebi.ac.uk/ena) under study numbers PRJEB33768, PRJEB33779 and PRJEB33780.…”
Section: Methodsmentioning
confidence: 99%
“…Sequencing reads were mapped to the reference genome sequence from C. difficile strain R20291 (sequence accession number FN545816) by using BWA-MEM and sequence variation was detected by applying VarScan2 as reported previously [46]. Sequence variation likely generated by recombination was detected through analysis with ClonalFrameML [47] and removed prior to determination of pairwise sequence distances [15] and to construction of maximum-likelihood phylogenetic trees with RAxML (version 8.2.9) [48].…”
Section: Methodsmentioning
confidence: 99%
“…2018). The Wilcoxon–Mann–Whitney test using Benjamini–Hochberg correction was used for statistical analyses (Steglich et al. 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies also suggest that CD630_ 08760 may function as a tyrosine transporter per its homology to the CodY-regulated neighbor gene, CD630_08730 (36). Furthermore, Steglich et al (37) observed decreases in tyrosine uptake and Stickland fermentation in clinical isolates lacking CD630_08760 and CD630_08780.…”
Section: Assignment Of Putative Functions To Genes In Egrin Modulesmentioning
confidence: 99%